METHODOLOGY OF RESEARCH AND TRAINING IN AIR NAVIGATION SOCIO-TECHNICAL SYSTEM - Kharchenko, Volodymyr; Shmelova, Tatyana; Sikirda, Yuliya (Proceedings of National Aviation University (archive), 2018)
Purpose: on the basis of professional and non-professional factors formalization, designing of models of decision making by Air Navigation System’s human-operator and flight situation development to work-out the methodology of research and training in Air Navigation Socio-technical System. Methods: systemic analysis, reflexive theory, network planning, decision tree, Markov network, GERT network, neural network, expert method. Results: the Air Navigation System has been presented as a complex Socio-technical System. The influence of the professional factors (knowledge, skills, abilities, experience) as well as the factors of non-professional nature (individual-psychological, psycho-physiological and socio-psychological) on the decision making by Air Navigation System’s human-operator has been defined. Graphical-analytical, deterministic, stochastic, reflexive, neural network models of decision making by Air Navigation System’s human-operator and flight situation development have been obtained. The program complex “Prompt” which operative and timely selection of the optimal flight completion strategy in the unusual situations required an aircraft forced landing has been created. Methodology of research and training in Air Navigation Socio-technical System has been developed. Discussion: the result of the evaluation of non-professional factors is determination the socio-psychological impact on human-operator’s decision making by identifying the preferences, diagnostics the individual-psychological qualities of human-operator in the development of flight situation, monitoring of the human-operator’s psycho-physiological indicators (emotional state). The proposed models will allow timely diagnosing and predicting the possible actions of human-operator in the expected and unexpected conditions of aircraft operation. The algorithms and methodology for analysis of situation development under influence of decision making by human-operator can be used in other technogenous production.